1999
DOI: 10.1002/(sici)1521-3773(19990503)38:9<1239::aid-anie1239>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Strong N−H⋅⋅⋅O Hydrogen Bonding in a Model Compound of the Catalytic Triad in Serine Proteases

Abstract: Low-barrier hydrogen bond (LBHB) involvement in enzyme catalysis is examined by analysis of experimental nuclear and electron densities of a model compound for the catalytic triad in serine proteases (shown schematically), which is based on a cocrystal of betaine, imidazole, and picric acid. The three short, strong N-H⋅⋅⋅O hydrogen bonds in the structure have varying degrees of covalent bonding contributions suggesting a gradual transition to the LBHB situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 6 publications
4
30
1
Order By: Relevance
“…2). [34] Furthermore, such a direct incorporation process not only leads to strongly bound chromophore probes with a higher loading capacity onto the pore surfaces, but also enhances the accessibility of the DTAR and DPAP probes to Cd 2+ ions, [30,34] which leads to transduction of an optical color signal as a response to the DTAR/DPAP-Cd 2+ binding events (Fig. 4).…”
Section: Design Of Dtar-or Dpap-probe Cage Nanosensors (2 and 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…2). [34] Furthermore, such a direct incorporation process not only leads to strongly bound chromophore probes with a higher loading capacity onto the pore surfaces, but also enhances the accessibility of the DTAR and DPAP probes to Cd 2+ ions, [30,34] which leads to transduction of an optical color signal as a response to the DTAR/DPAP-Cd 2+ binding events (Fig. 4).…”
Section: Design Of Dtar-or Dpap-probe Cage Nanosensors (2 and 3)mentioning
confidence: 99%
“…[21][22][23] Although the post grafting approaches can control the potential leaching of the incorporated probes into the sample solution, [22,[32][33][34] remaining challenges in these post-grafting techniques of probe-based chemical sensors include the ability to achieve flexibility of the specific activity of the electron acceptor/donor strength of the molecular probes. This mobility might easily generate and transduce an optical color signal as a response to probe-metal analyte binding events.…”
Section: Building-block Approach For Design Of the Dpc-probe Nanosensmentioning
confidence: 99%
“…The results indicated that the stability of the fabricated membrane strips when the incorporated azo probes had long-chain hydrophobic tails was for one year or even longer, thus eliminating the necessity for the high cost of silane or thiol coupling agents as surface modifiers during the design of the nanosensor strips. [15,21] The X-ray diffraction (XRD) patterns ( Fig. 2) of the membrane discs and strips show broad and well-resolved diffraction peaks that tentatively led to the assignment of the wormhole and ordered cubic Fd3m geometries, respectively.…”
Section: Full Papermentioning
confidence: 95%
“…[15][16][17][18][19]21] The results show that fast response times (where 10 min t R 15 min, at 25 8C) were features of the probe-Hg II ion complexation reactions in these nanosensor strips. In turn, an extension in the t R was observed with the wormhole membrane sensor arrays 1-3 (see Fig.…”
Section: Full Papermentioning
confidence: 99%
“…Intensity data for all the six crystals were collected using Mo Ka (k = 0.71073 Å) radiation on a Bruker SMART APEX diffractometer equipped with CCD area detector either at 293 K or at 100 K. The data integration and reduction were processed with SAINT [33] software. An empirical absorption correction was applied to the collected reflections with SADABS [34]. The structures were solved by direct methods using SHELXTL [35] and were refined on F 2 by the full-matrix least-squares technique using the SHELXL-97 [36] package.…”
Section: X-ray Crystallographymentioning
confidence: 99%